Efficacy of hot yoga as a heat stress technique for enhancing plasma volume and cardiovascular performance in elite female field hockey players - Perrotta, A. S.; White, M. D.; Koehle, M. S.; Taunton, J. E.; Warburton, D. E. R. (The Journal of Strength and Conditioning Research, 2018)
This investigation examined the efficacy of hot yoga as an alternative heat stress technique for enhancing plasma volume percentage (PV%) and cardiovascular performance. Ten international caliber female field hockey players completed six 60-minute hot yoga sessions using permissive dehydration over 6 days, followed by a 6-day national team camp. Changes in PV% were examined throughout the intervention and postintervention period. A graded maximal exercise test was performed in a thermoneutral environment (23.2 ± 1.0° C) 24 hours before and 24 hours after intervention. Six days of hot yoga initiated a moderate state of hypovolemia (PV% = -3.5%, 90% confidence limit [CL] [-6.9 to -0.13]), trivial improvements in maximal aerobic power (VO2max) (effect size [ES] = 0.06, 90% CL [-0.16 to 0.28]), and run time to exhaustion (ES = 0.11, 90% CL [-0.07 to 0.29]). Small meaningful improvements were observed in running speed (km·h-1) at ventilatory threshold (VT1) (ES = 0.34, 90% CL [-0.08 to 0.76]), VT2 (ES = 0.53, 90% CL [-0.05 to 1.1]), along with adaptations in the respiratory exchange ratio during high-intensity exercise (ES = -0.25, 90% CL [-0.62 to 0.12]). A large plasma volume expansion transpired 72 hours after intervention (PV% = 5.0%, 90% CL [1.3-8.7]) that contracted to a small expansion after 6 days (PV% = 1.6%, 90% CL [-1.0 to 4.2]). This investigation provides practitioners an alternative heat stress technique conducive for team sport, involving minimal exercise stress that can preserve maximal cardiovascular performance over periodized rest weeks within the yearly training plan. Furthermore, improvements in submaximal performance and a delayed hypervolemic response may provide a performance-enhancing effect when entering a 6-day competition period.